Health / A Multimedia Source Guide - Ash John; Stevenson Michael (R. R. Bowker Company, 1976)
Preface, Introduction, Associations and Societies and Foundations, Audiovisual Producers and Distributors, Book Dealers, City and State and Federal Agencies, Libraries and Information Services, Pharmaceutical and Other Companies, Publishers, Research Institutes, Source Index, Index to Free Inexpensive Material, Subject Index.